Transdermal colorimetric patch for hyperglycemia sensing in diabetic mice. (April 2020) - Wang, Zejun; Li, Hongjun; Wang, Jinqiang; Chen, Zhaowei; Chen, Guojun; Wen, Di; Chan, Amanda; Gu, Zhen
Abstract: The integration of sampling and instant metabolite readout can fundamentally elevate patient compliance. To circumvent the need for complex in-lab apparatus, here, an all-in-one sampling and display transdermal colorimetric microneedle patch was developed for sensing hyperglycemia in mice. The coloration of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) is triggered by the cascade enzymatic reactions of glucose oxidase (GOx) and horseradish peroxidase (HRP) at abnormally high glucose levels. The HRP in the upper layer is biomineralized with calcium phosphate (CaP) shell to add a pH responsive feature for increased sensitivity as well as protection from nonspecific reactions. This colorimetric sensor achieved minimally invasive extraction of the interstitial fluid from mice and converted glucose level to a visible color change promptly. Quantitative red green and blue (RGB) information could be obtained through a scanned image of the microneedle. This costless, portable colorimetric sensor could potentially detect daily glucose levels without blood drawing procedures.